Therapeutic conduct in postmenopausal women with different forms of urinary incontinence - Szymczak, Maria; Majchrzycki, Marian (Menopause Review/Przegląd Menopauzalny, 2013)
Urinary incontinence is a serious medical, social, economic and therapeutic issue. This paper is a review of current ideas on the influence of menopause and age on the risk of incontinence. The paper presents selected physiotherapeutic methods used in the treatment of urinary incontinence. The most commonly used methods include: urogenital diaphragm exercises (Kegel exercise), behavior therapy (biofeedback, bladder training), electrostimulation, magnetic therapy and mechanical tools (e.g. vaginal cones). The importance of patient and health professional prophylaxis is also discussed.